2017
DOI: 10.1042/bcj20160825
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1 Tat potently stabilises Mdm2 and enhances viral replication

Abstract: Murine double minute 2 (Mdm2) is known to enhance the transactivation potential of human immunodeficiency virus (HIV-1) Tat protein by causing its ubiquitination. However, the regulation of Mdm2 during HIV-1 infection and its implications for viral replication have not been well studied. Here, we show that the Mdm2 protein level increases during HIV-1 infection and this effect is mediated by HIV-1 Tat protein. Tat appears to stabilise Mdm2 at the post-translational level by inducing its phosphorylation at seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 67 publications
(70 reference statements)
2
32
0
Order By: Relevance
“…An siRNA screen based on the most differentially expressed genes from our transcriptomic analysis in virus-infected MDMs further revealed that MDM2 acts as one of the rare positive regulators of HIV-1 infection in this cell type (9). Some previous studies performed with immortalized cell lines have shown that MDM2 can regulate HIV-1 infection by interacting with viral proteins such as Tat and Vif (21,22,34). However, our results suggest that MDM2 can shape the cellular environment by itself, thereby affecting the susceptibility of MDMs to productive HIV-1 infection.…”
Section: Discussionmentioning
confidence: 70%
“…An siRNA screen based on the most differentially expressed genes from our transcriptomic analysis in virus-infected MDMs further revealed that MDM2 acts as one of the rare positive regulators of HIV-1 infection in this cell type (9). Some previous studies performed with immortalized cell lines have shown that MDM2 can regulate HIV-1 infection by interacting with viral proteins such as Tat and Vif (21,22,34). However, our results suggest that MDM2 can shape the cellular environment by itself, thereby affecting the susceptibility of MDMs to productive HIV-1 infection.…”
Section: Discussionmentioning
confidence: 70%
“…Tat is also ubiquitinated through Lys-63-linked ubiquitin chains for enhancing its transcriptional activity (41). Lys-63-linked Tat ubiquitination is also carried out by cellular E3 ubiquitin ligase, MDM2, and Tat translocates MDM2 into the nucleus to protect it from proteasomal degradation (42). Tat also uses MDM2 for suppressing immune activation by promoting IRF-1 degradation (34).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as described earlier 28 , 29 . The primary antibodies used were anti-AKT, anti-S473 phopsho-AKT, anti-GAPDH, anti-PARP, anti-Caspase-3, anti-ERK1/2, anti-phospho 44/42 ERK1/2, anti-phospho-SAPK/JNK, anti-SAPK/JNK, anti-SP1, anti-LC3B (Cell Signalling Technology), anti-p24 (Cat No.…”
Section: Methodsmentioning
confidence: 99%